Construction of a synergy combination model for turmeric (Curcuma longa L.) and black pepper (Piper nigrum L.) extracts: enhanced anticancer activity against A549 and NCI-H292 human lung cancer cells - Cho, HyunKi; Park, Chang Gyun; Lim, Heung-Bin (Current issues in molecular biology, 2024)
Extensive research on medicinal herbs for bioactive compounds proposes that they could replace synthetic drugs, reducing side effects and economic burdens. Especially, interest in the synergistic benefits of natural products is increasing, implying that their combined use may enhance therapeutic effectiveness. This study aimed to explore the synergetic effects of turmeric (Curcuma longa L.) and black pepper (Piper nigrum L.) extract on lung normal (MRC-5) and cancer (A549 and NCI-H292) cell lines. The turmeric extract (TM) only affected the lung cancer cell lines, but it had no impact on the MRC-5 cell line. On the other hand, the black pepper extract (BP) did not cause any damage to either the lung normal or cancer cell lines, even at concentrations of up to 400 µg/mL. Response surface methodology was used to predict the ideal synergistic concentrations (EC50) of TM and BP, which were found to be 48.5 and 241.7 µg/mL, respectively. Notably, the selected condition resulted in higher cytotoxicity compared to the exposure to TM alone, indicating a potent synergetic effect. The rate of curcumin degradation under this combined treatment was significantly decreased to 49.72 ± 5.00 nmol/h/µg for A549 cells and 47.53 ± 4.78 nmol/h/µg for NCI-H292 cells, respectively, as compared to curcumin alone. Taken together, this study confirmed the potent synergistic effect of TM and BP on lung cancer cell lines. Further research is required to identify their specific synergetic mechanisms. Our findings provide crucial foundational data on the synergistic effects of TM and BP.
Gesehen am 12.12.2024